DETERMINAN KEPUTUSAN NASABAH MEMILIH PEMBIAYAAN KPR (Studi pada Bank BTN Syariah Langsa) - Nurkamilia; Muhammad Salman; Afrah Junita (Jurnal Mahasiswa Akuntansi Samudra, 2025)
This study aims to determine the determinants of customer decisions in choosing mortgage financing (a study at Bank BTN Syariah Langsa). The objects of this study were customers who took mortgage products at Bank BTN Syariah Langsa Branch from 2020-2023. The data collection method was through the results of questionnaires that had been distributed to respondents. The data analysis method used in this study was multiple linear regression analysis using SPSS (Statistical Package for the Social Science) software. The results of this study indicate that the price variable has a positive and significant effect on customer decisions, the location variable has a positive and significant effect on customer decisions, the promotion variable has a negative and significant effect on customer decisions, the Islamic financial literacy variable has a positive and significant effect on customer decisions, simultaneously price, location, promotion and Islamic financial literacy have a significant effect on customer decisions. Limitations of this study The analysis used is limited to the relationship between variables in the specified model, so it has not explored other more complex factors. The analysis only uses quantitative methods with questionnaires, so it has not delved deeper into the motivations and personal reasons of customers. The study was conducted solely on BTN Syariah Langsa's Sharia mortgage customers, so the results may not necessarily represent all BTN Syariah customers in Indonesia. It is recommended that future researchers explore other independent variables that are thought to significantly influence the dependent variable, thereby strengthening the research findings and generating new, beneficial findings for various parties. The study should not only focus on BTN Syariah Langsa but also on other branches or comparisons with other Islamic banks to achieve more comprehensive research results.